Pengaruh Gamifikasi, Flow Experience, dan Perceived Enjoyment pada Niat Bertransaksi Pengguna Shopee - Ayu Desti Lestari; Alfizi; Puspita Lianti Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of gamification, flow experience, and perceived enjoyment on users’ transaction intention on the Shopee application in Banyumas Regency. The background of this research is based on the high national usage of Shopee, which does not necessarily align with the utilization of its interactive features, such as gamification, in semi-urban areas. This study uses a quantitative approach with descriptive and causal research designs. Data were collected through questionnaires distributed to 100 respondents who are active Shopee users in Banyumas and have interacted with gamified features such as Shopee Tanam, Shopee Candy, and others. The data analysis technique used is multiple linear regression. The results show that gamification, flow experience, and perceived enjoyment each have a positive effect on transaction intention. Simultaneously, the three variables also significantly influence users' intention to transact on Shopee. These findings are expected to provide strategic insights for Shopee in improving the effectiveness of its interactive features and enhancing user loyalty, particularly in semi-urban areas.